2022
DOI: 10.3389/fimmu.2022.967487
|View full text |Cite
|
Sign up to set email alerts
|

The short-term and long-term effects of intranasal mesenchymal stem cell administration to noninflamed mice lung

Abstract: Mesenchymal stem cells (mesenchymal stromal cells; MSC)-based therapies remain a promising approach to treat degenerative and inflammatory diseases. Their beneficial effects were confirmed in numerous experimental models and clinical trials. However, safety issues concerning MSCs' stability and their longterm effects limit their implementation in clinical practice, including treatment of respiratory diseases such as asthma, chronic obstructive pulmonary disease, and COVID-19. Here, we aimed to investigate the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 40 publications
(41 reference statements)
0
1
0
Order By: Relevance
“…Recent studies have revealed that delivering human AT-MSCs intranasally to non-inflamed mouse lungs resulted in a low-grade lung inflammation with increased IFN-γ expression, weakened epithelial barrier integrity due to decreased tight junction proteins, activation of innate and adaptive immune responses with elevated IL-7 and T/B cell signaling pathways, and induced redox imbalance characterized by increased HIF1a signaling and superoxide radical degradation. These effects could be attributed to the activation of the recipient organ’s hypoxia pathways in vivo by the transplanted MSCs, which resulted in MSC apoptosis and then triggered a series of graft clearance reactions 132 . Third, the uncontrollable differentiation of MSCs during transplantation has become a safety hazard associated with its application.…”
Section: Conclusion and Future Perspectivementioning
confidence: 99%
“…Recent studies have revealed that delivering human AT-MSCs intranasally to non-inflamed mouse lungs resulted in a low-grade lung inflammation with increased IFN-γ expression, weakened epithelial barrier integrity due to decreased tight junction proteins, activation of innate and adaptive immune responses with elevated IL-7 and T/B cell signaling pathways, and induced redox imbalance characterized by increased HIF1a signaling and superoxide radical degradation. These effects could be attributed to the activation of the recipient organ’s hypoxia pathways in vivo by the transplanted MSCs, which resulted in MSC apoptosis and then triggered a series of graft clearance reactions 132 . Third, the uncontrollable differentiation of MSCs during transplantation has become a safety hazard associated with its application.…”
Section: Conclusion and Future Perspectivementioning
confidence: 99%